401 Environmental and Nutritional Implications of Agriculture without Animals. (7th December 2018) - White, R; Hall, M
Abstract: Increasing investigations into the environmental impact of agriculture have suggested livestock contribute to agricultural greenhouse gas emissions (GHG), inferring removal of livestock would enable significant reductions in agricultural GHG. The objective of this work was to summarize the GHG and collateral nutritional shifts associated with removing livestock from United States (U.S.) agriculture. Although the U.S. Environmental Protection Agency suggests livestock currently contribute 9% of total U.S. GHG, and 49% of agricultural GHG; the work of White and Hall (DOI: https://doi.org/10.1073/pnas.1707322114 ) suggests elimination of livestock from U.S. agriculture would only reduce total emissions by 2.6 to 2.9% (a 28 to 32% reduction in agricultural GHG). Concurrently, this shift in agricultural productivity would result in a food supply with insufficient supplies of essential vitamins, minerals, and fatty acids. A notable assumption of the assessment of White and Hall was that land-use in the US would be adjusted based on the current proportions of land use. This assumption resulted in corn and soy making up large portions of the grains (70%) and legumes (90%) being produced. An alternative assumption would be that land use in the U.S. could be adjusted to farm more fruits and vegetables. This scenario was evaluated in a follow-up letter by White and Hally (DOI: https://doi.org/10.1073/pnas.1720895115 ) and failed to meet the US population's requirement for vitamin B12, long-chain omega-3 and omega-6 fatty acids. Results of these investigations highlight the need to expand our assessments of the environmental-impact of the food production system to consider the broader picture and the collateral impacts of proposed changes in this system.